The Effectiveness of Sitaya Miniature Media on the Cognitive Abilities of Group B Children Aged 5–6 Years at Darussalam Islamic Kindergarten, Palangka Raya - Febrianty, Berliana Nansya; Fitriani, Ignatia Imelda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2025)
Learning media plays an important role in the teaching and learning process. The use of media is expected to create positive impacts, such as a more conducive learning environment, feedback, and optimal outcomes. The Sitaya Miniature Media represents a